Transcription factors in microcephaly - Lim, Youngshin (Frontiers in Neuroscience, 2023)
Higher cognition in humans, compared to other primates, is often attributed to an increased brain size, especially forebrain cortical surface area. Brain size is determined through highly orchestrated developmental processes, including neural stem cell proliferation, differentiation, migration, lamination, arborization, and apoptosis. Disruption in these processes often results in either a small (microcephaly) or large (megalencephaly) brain. One of the key mechanisms controlling these developmental processes is the spatial and temporal transcriptional regulation of critical genes. In humans, microcephaly is defined as a condition with a significantly smaller head circumference compared to the average head size of a given age and sex group. A growing number of genes are identified as associated with microcephaly, and among them are those involved in transcriptional regulation. In this review, a subset of genes encoding transcription factors (e.g., homeobox-, basic helix-loop-helix-, forkhead box-, high mobility group box-, and zinc finger domain-containing transcription factors), whose functions are important for cortical development and implicated in microcephaly, are discussed.